PENGARUH CURRENT RATIO, DEBT TO EQUITY, NET PROFIT MARGIN, RETURN ON ASSET TERHADAP HARGA SAHAM PADA INDUSTRI FARMASI YANG TERDAFTAR DI BEI TAHUN 2014-2018 - Fadli Kemal Wusurwut; Nur Hidayati; Anik Malikah (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The purpose of this study is to test the Current Ratio analysis, Debt to Equity, Net Profit Margin, and Asset Returns to Stock Prices. The sample in this study were 8 pharmaceutical companies listed on the Indonesia Stock Exchange. In this study the sampling technique used purposive sampling. The analysis technique used in this study is multiple linear analysis. The results of this study indicate that the Current Ratio has a significant influence on Stock Prices, Debt to Equity to Stock Prices, Net Profit Margin to Stock Prices. The sample in this study were 8 pharmaceutical companies listed on the Indonesia Stock Exchange. In this study the sampling technique used purposive sampling. The analysis technique used in this study is multiple linear analysis. Current Ratio, Debt to Equity, Net Profit Margin and Return On Asset have a significant influence on Stock Prices.Keywords: Current Ratio, Debt to Equity, Net Profit Margin, Return on Asset, Stock Price.